Cytokine and Chemokines Alterations in the Endemic Form of Pemphigus Foliaceus (Fogo Selvagem) - Timóteo, Rodolfo Pessato; Silva, Marcos Vinicius; da Silva, Djalma Alexandre Alves; Catarino, Jonatas Da Silva; Alves, Fernando Henrique Canhoto; Rodrigues Júnior, Virmondes; Roselino, Ana Maria; Sales-Campos, Helioswilton; Oliveira, Carlo José Freire (Frontiers in Immunology, 2017)
Abstract Introduction: The endemic form (Fogo selvagem-FS) of Pemphigus foliaceus is an autoimmune disease characterized by the presence of IgG autoantibodies against desmoglein-1. Despite the array of findings, the role of chemokines and cytokines that dictate the immune response and disease outcome is still poorly investigated. Materials and methods: Serum from 64 patients diagnosed with FS was used to draw and establish the levels of these molecules on this disease and establish the levels of these molecules with the severity of FS, and influence of treatment. Results: In comparison to healthy subjects, FS patients, newly diagnosed and still without therapeutic intervention, had higher levels of IL-22 and CXCL8, and reduced levels of IFN-γ, IL-2, IL-15 and CCL-11. Furthermore, treatment using immunosuppressant drugs augmented the production of IFN-γ, IL-2, CCL-5 and CCL-11 besides of reducing the levels of IL-22 and CXCL-10. Immunosuppressive therapy seemed to have long lasting effects on the production of higher amounts of IFN-γ, IL-2, and CCL-5, besides of keeping lowered the levels of IL-22 in remission FS patients. Conclusion: Taken together, our findings suggest a putative role of IL-22 in the pathogenesis of FS. Finally, data presented here may contribute for better understanding the immune aspects that control disease outcome.